THE EFFECTIVENESS OF FINANCIAL MANAGEMENT OF THE LAMU VILLAGE GOVERNMENT, TILAMUTA DISTRICT BOALEMO DISTRICT - Wirna Mayulu; Darman; Sukrianto (Jurnal Ilmu Manajemen dan Bisnis, 2024)
In a period of several years from 2018 to 2022, it was found that village financial management had not been implemented optimally. The research objectives are (1) To find out the financial planning of the Lamu Village Government, Tilamuta District, Boalemo Regency. (2) To find out the financial implementation of the Lamu Village Government, Tilamuta District, Boalemo Regency. (3) To find out the financial administration of the Lamu Village Government, Tilamuta District, Boalemo Regency. (4) To find out the financial reporting of the Lamu Village Government, Tilamuta District, Boalemo Regency. (5) To find out the financial accountability of the Lamu Village Government, Tilamuta District, Boalemo Regency. The research method used is descriptive research and a qualitative approach. Data collection techniques are observation, in-depth interviews and documentation. Data analysis techniques are data reduction, data presentation and conclusions. The results of the research are (1) Village financial planning in Lamu Village has not been running effectively because there are still disputes over programs which have often occurred between the community and the Lamu Village Government. (2) The implementation of village finances in Lamu Village has not been running effectively because the planned programs often do not match the conditions in the field. (3) The administration of village finances in Lamu Village has been running effectively as proven by the Village Government following procedures in policies that are implemented in accordance with existing regulations. (4) Village financial reporting in Lamu Village has not been running effectively because reporting is often hampered due to networks in village financial reporting. (5) Village financial accountability in Lamu Village has been running effectively, because the Lamu Village Government will make inputs on time so as not to exceed the target time